Insights into the Concepts of the Curriculum - Abebe, Bekele (The Ethiopian Journal of Education, 2024)
In the process of the curriculum development two important factors are given considerable attention; the defmition of the term curriculum and the 1\'(1\'\ by which educational objectives are determined. The paper examines these two issues briefly.